Practices of the I'adah Zuhur after Friday Prayers in Aceh Besar District: An Analysis with the perspectives of Islamic Law Approaches - Muthalib, Salman Abdul; Amri, Furqan; Ali, Bukhari (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
This study discusses the practice of i'adah dzuhur after the Friday Prayers in Aceh Besar. I'adah dzuhur is carried out by some people as they see that the performance of Friday Prayers is considered to have ignored several conditions. This leads to some people’s decisions to re-perform the dzuhur prayer. This fact encourages the author to explore reasons that some people consider carrying out the i'adah dzuhur after Friday prayers. In addition, the performance is i'adah dzuhur was also driven by perspectives of Muslim scholars graduated from Islamic traditional boarding schools suggesting that the performance of Friday praying has yet to meet certain level of validity. This study is an empirical juridicial study using the Islamic legal approach. The data for the study was collected through interviews, observation and document analysis. In addition, the data was analyzed using qualitative data analysis procedures. The results showed that the performance of Friday prayers in Aceh Besar has met the rules as mandated in the fiqh. However, some people in Aceh Besar are cautious on the eligibility of the Friday prayer performances. This caution is in regard with the two requirements for the validity of Friday: First, the location between mosques should be adjacent with each other. Second, there should be the minimum number of 40 Friday prayer congregations, and all of them should be well educated on the nature of Friday prayers. As a result of being unsure about the fulfillment of these two conditions and caution (ihtiyati), some people perform the i'adah dzuhur after Friday. Such communal understanding is influenced by the alumni of Islamic traditional Boarding schools (dayah) due to several factors. First, the emergence of Islamic figures from the traditional Islamic boarding school; second, the alumni has been active in various socio-religious activities, and third, the alumni have gained some charisma.